2014
DOI: 10.1080/03069885.2014.920077
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking deindustrialisation and male career crisis

Abstract: The decline in manufacturing and growth of service based jobs has prompted many social theorists to argue that the ability of working class men to construct meaningful and rewarding careers is becoming ever more limited. Despite using the universal label 'working class' the experience of skilled working class men has been largely ignored. This article explores 26 work history interviews collected from 14 former Royal Dockyard tradesmen in South East England and 12 of these men's sons and grandsons. Findings fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
1

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…This article arose from an intergenerational study of familial working-class men's negotiation of deindustrialization. This research found a pattern of slow upward social mobility within three generations, as men moved from unskilled to skilled trade employment and finally white collar, mostly managerial, employment (Ackers, 2014). In these men's accounts, each generation communicated 'double messages' to their sons that suggested they should move into employment a step up the occupational ladder from their fathers but without forgetting the values of their working-class backgrounds.…”
Section: Introductionmentioning
confidence: 84%
See 1 more Smart Citation
“…This article arose from an intergenerational study of familial working-class men's negotiation of deindustrialization. This research found a pattern of slow upward social mobility within three generations, as men moved from unskilled to skilled trade employment and finally white collar, mostly managerial, employment (Ackers, 2014). In these men's accounts, each generation communicated 'double messages' to their sons that suggested they should move into employment a step up the occupational ladder from their fathers but without forgetting the values of their working-class backgrounds.…”
Section: Introductionmentioning
confidence: 84%
“…To explore how deindustrialization was affecting intergenerational male identities, this study only interviewed men. As a result, this research cannot comment on how social mobility is experienced in relationships between female or mixed familial kin such as father–daughter relationships (for a more in depth discussion of this topic, see Ackers, 2014, 2019). Rather, this study is restricted to discussing fathers’, sons’ and grandsons’ generational negotiation of social mobility.…”
Section: The Research Project and Methodsmentioning
confidence: 99%
“…The first sample was composed of 14 former dockyard craftsmen and the second 14 of these men's sons and grandsons. This research found that neither sample experienced a rupture or crisis in their gendered identities due to the closure of the dockyard (Ackers, , ). Instead, these men reinterpreted and resituated cross‐generational themes together to retain a sense of secure male work identity while navigating a period of employment change.…”
Section: Introductionmentioning
confidence: 94%